Intermittent supplementation with Akkermansia muciniphila and galactooligosaccharides modulates Alzheimer’s disease progression, gut microbiota, and colon short-chain fatty acid profiles in mice - Kunevičius, Arnas; Vijaya, Akshay Kumar; Atzeni, Alessandro; Mingaila, Jonas; Šimoliūnė, Ieva; Jamontas, Rapolas; Keževičiūtė, Emilija; Gueimonde, Miguel; Meškys, Rolandas; Baltriukienė, Daiva; Arboleya, Silvia; Burokas, Aurelijus (Frontiers in Aging Neuroscience, 2025)
BackgroundBidirectional communication and mutual regulation between the gastrointestinal tract and the CNS is facilitated through the gut-brain axis. Recent studies have found reduced diversity of the gut microbiota in Alzheimer’s disease (AD) patients, and animal models suggest microbial involvement in amyloid beta peptide (Aβ) accumulation. Modulation of the gut microbiota by new-generation probiotics represents a novel treatment strategy to alleviate the symptoms and slow the progression of AD.MethodsIn this study, the therapeutic effect of the probiotic Akkermansia muciniphila and the prebiotic galactooligosaccharides (GOS) was investigated in the APP/PS1 mouse model. After 7 months of triweekly administration, we evaluated physiological parameters, glucose metabolism, and behavioral outcomes. Additionally, we assessed gut microbiota diversity and composition, short-chain fatty acid (SCFA) concentrations in the cecum, Aβ load in the hippocampus and prefrontal cortex, and microglial abundance in the hippocampus.ResultsA. muciniphila and GOS administration normalized fasting glucose levels, glucose metabolism, and intestinal transit time to wild-type levels. Furthermore, supplementation reduced anxiety, improved long-and short-term memory, and partially restored activity levels. It also regulated SCFA concentrations in the cecum, improved the richness of the gut microbiota, and normalized abundance of microglia in the hippocampus, indicating reduced neuroinflammation.ConclusionThese findings suggest that long-term administration of A. muciniphila and GOS effectively improves metabolic health and modulates symptoms of AD in the APP/PS1 mouse model.